O exílio de Stephen Dedalus: o percurso do nome próprio em Um retrato do artista quando jovem e Ulysses - Carolina Esselin de Sousa Lino (2017)
The work of this dissertation follows the trajectory of Stephen Dedalus in A Portrait of the Artist as a Young Man and in Ulysses, both of James Joyce, focusing on the nature of his exile and the course of his proper name, mainly based on the contributions of the philosopher Jacques Derrida.